Public cybersecurity as guarantee of the exercise of rights - Galán, Carlos Manuel (2016)
The development of fundamental human rights contained in the texts of the Universal Declarations and the Constitutions of democratic states requires that information systems that support its exercise are permanently operational. However, this need is constantly violated by many cyberattacks that, in the heart of the matter, seek to undermine the free exercise of such rights. It is in this environment where public cybersecurity, understood as the set of legal regulations, methods, procedures and tools, finds its reason for being and is configured as the only appropriate means of ensuring social coexistence in accordance with the principles of the Rule of Law.